1998
DOI: 10.1088/0964-1726/7/2/002
|View full text |Cite
|
Sign up to set email alerts
|

In-situprocess and condition monitoring of advanced fibre-reinforced composite materials using optical fibre sensors

Abstract: This paper presents a general overview of a number of optical fibre sensor systems which have been developed and used in advanced fibre-reinforced composites for in-situ process and condition monitoring. The in-situ process monitoring techniques were optical-fibre-based evanescent wave spectroscopy, transmission near-infrared spectroscopy and refractive index monitoring. The optical fibre sensors were successful in tracking the cure reaction. The condition monitoring of advanced fibre-reinforced composites was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 39 publications
0
64
0
Order By: Relevance
“…Therefore, quality assurance of large-scale composite structures is necessary, and there is an urgent need to develop effective cure monitoring techniques for composite materials since the quality of the materials is very dependent on their cure processes [1][2][3]. Several cure monitoring techniques are utilized for composite materials, such as differential scanning calorimetry [4], dielectrometry [5], and point type optical fiber sensors including extrinsic Fabry-Perot type sensors [6,7], Raman spectroscopy [8], and fiber Bragg grating (FBG) sensors [9][10][11]. Among these techniques, optical fiber sensors are very useful for strain and temperature monitoring of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quality assurance of large-scale composite structures is necessary, and there is an urgent need to develop effective cure monitoring techniques for composite materials since the quality of the materials is very dependent on their cure processes [1][2][3]. Several cure monitoring techniques are utilized for composite materials, such as differential scanning calorimetry [4], dielectrometry [5], and point type optical fiber sensors including extrinsic Fabry-Perot type sensors [6,7], Raman spectroscopy [8], and fiber Bragg grating (FBG) sensors [9][10][11]. Among these techniques, optical fiber sensors are very useful for strain and temperature monitoring of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, a RFID sensor tag to evaluate the accumulation of fatigue damage has not been presented because it is difficult to combine the RFID system and traditional fatigue assessment techniques, such as continuous strain monitoring by strain gage or FBG (Fiber Bragg Grating) sensor. [11][12][13] The estimation of fatigue damage of structures is very important to avoid fractures due to their aging degradation. Therefore, RFID-type fatigue sensor is strongly required for this sensor network.…”
Section: Introductionmentioning
confidence: 99%
“…It was even concluded that optical fibre Bragg sensors were more reliable than classical strain gauges [1]. Doyle et al [3] experimented on the use of fibre optic sensors for tracking the cure reaction of a fibre reinforced epoxy, with success. They also successfully demonstrated the feasibility of these sensors for monitoring the stiffness reduction due to fatigue damage, but for thermosetting matrix.…”
Section: Introductionmentioning
confidence: 99%